MEASUREMENT INSTRUMENTS FOR ASSESSING CRITICAL THINKING SKILLS IN LEARNING: A LITERATURE REVIEW - Simamora, Lika Nurmala Sari; Siburian, Jodion; Lely Mardiyanti (STKIP Citra Bakti, 2026)
This study aims to systematically examine the range of instruments employed in the assessment of critical thinking. Critical thinking is conceptualized as a higher-order cognitive process involving the analysis, application, evaluation, and synthesis of information. The study adopts a Systematic Literature Review (SLR) approach, drawing on 15 peer-reviewed articles published between 2020 and 2025 and indexed in Scopus (Q1–Q4) and SINTA (S1–S4). The articles were retrieved through database searches using Google Scholar, GARUDA, and SINTA, employing keywords such as “critical thinking instruments,” “development,” and “critical thinking assessment.” The review process comprised three stages: identification, screening, and eligibility assessment. Articles were initially screened based on their titles and abstracts, and duplicate records were subsequently removed. The analysis encompassed a wide range of critical thinking assessment instruments, including written tests (e.g., multiple-choice, essay-based, and complex true–false formats) as well as non-test instruments, such as psychometric scales, computer-based assessments, dialogic instruments, and rubric-based qualitative assessments. The findings indicate that no single instrument is capable of comprehensively capturing all dimensions of critical thinking. Rather, each instrument demonstrates particular strengths and limitations in assessing specific components, such as analysis, evaluation, and reasoning. Accordingly, the selection of assessment instruments should be carefully aligned with the research objectives, the instructional context, and the specific critical thinking indicators to be measured.